Discrete-Event Simulation of Road Traffic Congestion to Support Green Supply Chain - Zulqarnain Hakim Abd Jalal, Muhammad; Laailatul Hanim Mat Desa, Wan; Kamal Mohd Nawawi, Mohd; Khalild, Ruzelan (International Journal of Engineering and Technology, 2018)
This paper presents a discrete-event simulation (DES) study on road traffic intersections at one of the fastest developing towns in Kedah, Malaysia. Inefficient traffic light control (TLC) of the existing system contributes to the road traffic congestion (RTC) especially during peak hours, which leads to environment pollution. With the increasing awareness about environmental issues, businesses and governments increasingly want to reduce the pollution which leads to green supply chain. RTC can be caused by a temporary obstruction or a permanent capacity bottleneck in the network itself. A DES model was developed based on current system and then â€œwhat-ifâ€ scenario was analyzed to check whether improvement would be achieved. Results from the analysis show that average waiting time and number in queue could be reduced specifically at two of the lanes under study.Â Â Â